The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.4142/jvs.2006.7.3.303
|View full text |Cite
|
Sign up to set email alerts
|

Pygomelia or supernumerary limbs in a crossbred calf

Abstract: A crossbred (Sindhi × local indigenous) calf that was 12 days old was admitted to the Teaching Veterinary Hospital, Chittagong Government Veterinary College, Bangladesh, with two accessory hind limbs attached to the pelvic region in between the hind legs. This was clinically identified as a congenital anomaly popularly called pygomelia. The pygomelia was successfully corrected by surgical excisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 3 publications
(2 reference statements)
3
17
0
2
Order By: Relevance
“…The susceptibility to an injurious environmental or to genetic agents varies with the stage of development and between species, and the susceptibility decreases with the advancement of foetal age. The signalment and clinical signs of the SEL and polydactyly in our cases are in full agreement with previous reports of similar cases in cattle (Hiraga et al, 1989;Fourie, 1990;Kim et al, 2001;Bahr et al, 2003;Rahman et al, 2006). The first morphological evidence of a limb during embryonic development is the emergence of a bulge at the appropriate level in the lateral body wall.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The susceptibility to an injurious environmental or to genetic agents varies with the stage of development and between species, and the susceptibility decreases with the advancement of foetal age. The signalment and clinical signs of the SEL and polydactyly in our cases are in full agreement with previous reports of similar cases in cattle (Hiraga et al, 1989;Fourie, 1990;Kim et al, 2001;Bahr et al, 2003;Rahman et al, 2006). The first morphological evidence of a limb during embryonic development is the emergence of a bulge at the appropriate level in the lateral body wall.…”
Section: Discussionsupporting
confidence: 82%
“…Congenital anomalies with accessory limbs and digits occur very rarely in cattle and there are few, if any, reports on such incidences in Korea. The animals with supernumerary ectopic limbs and supernumerary digits can survive successfully with normal locomotion and better aesthesis if the surgical excision is performed under proper aseptic conditions and appropriate postoperative care is taken (Hossain et al, 1980;Singh et al, 1989;Fourie, 1990;Rahman et al, 2006). The cases reported here describe the successful surgical excision of supernumerary limbs in four Korean indigenous calves.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It has been reported that animals with supernumerary digits can survive successfully with normal locomotion and better aesthesis if the surgical excision is performed under proper aseptic conditions and appropriate postoperative care is provided (Hossain et al 1980;Singh et al 1989;Fourie 1990;Rahman et al 2006). In the described case the surgical procedure was indicated for cosmetic reasons.…”
Section: Discussionmentioning
confidence: 94%
“…Genel durumun kötü olması, eklenti bacakların alınması ile birlikte başta medulla spinalis olmak üzere diğer hayati önem taşıyan organlara zarar verecek olması, onarılamayacak büyüklükte defektlerin (hernia ventralis, hernia umblikalis, kolon agenezisi gibi) polimeli ile birlikte bulunması gibi durumlarda cerrahi sağaltım yerine hayvanın kesime gönderilmesi gerekir, bunun dışında kalan durumlarda ve erken yapılan cerrahi girişimler başarılı olur (2,8).…”
unclassified